Science on a Salad Plate? Thinking About the Representation of Natural History in the Canadian Historic Dinner Service Project - Cronin, Keri (Scientia Canadensis, 2008)
AbstractThe Women’s Art Association of Canada marked the 400th anniversary of John Cabot’s “discovery” of Canada (celebrated in 1897) through the production of the “Canadian Historic Dinner Service.” The high-profile project, which resulted in a set of hand-painted porcelain dinnerware, was a celebration not only of nation-building, but also of the natural history of the country. Visual reference material provided to the women selected to create the individual pieces included photographs, natural history texts, and illustrations that W.H. Bartlett produced for Canadian Scenery earlier in the century. This article explores this visual reinterpretation of Canada’s natural history in order to raise questions about how a recontextualization of scientific material shapes narratives of nation and nature in the ‘New World’.